Assessing the Effect of Slope Geometry on Slope Factor of Safety in the Elgon Sub-Region. - Barasa, Emmanuel (Kabale University, 2025)
This research project delved into the crucial interplay between slope geometry and slope stability in the Elgon sub-region. The study encompasses a comprehensive assessment employing various geotechnical tests, including Particle Size Distribution (PSD), Direct Shear Test, Core Cutting Test, and Atterberg Limits Test. The geotechnical data, coupled with advanced analysis using Geo-Slope software, elucidates the dynamic relationship between slope geometry and the Factor of Safety of slopes. The findings offer valuable insights into the influence of slope geometry on slope stability, providing a basis for informed geotechnical engineering practices in the challenging terrain of Elgon. This research serves as a significant contribution to the understanding of regional geotechnical dynamics and sets the stage for enhanced slope management strategies in similar geologic settings.